Controversial Policies and the Usefulness of Nonprofit, Private and Public Sector Partnerships: Introducing An Assisted Suicide Service in Ontario - Brock, Kathy (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2012)
This article addresses whether a partnership between the public, non-profit, and private sectors represents a feasible solution for dealing with contentious and symbolic public policy issues in the provision of assisted suicide service in Ontario. The first section outlines key characteristics of mature and integrated relationships among the three sectors. The second determines the parameters of acceptable policy by exploring the intersection between economic drivers and public opinion on assisted suicide:the Ontario government is intent on reducing health care expenditures, while public opinion increasingly favours end-of-life options but is wary of state pressure upon individuals to choose an early death in order to save on costly medical interventions. The third section demonstrates how a trisectoral partnership could build a model of an assisted suicide policy and service in Ontario by incorporating design elements from the Dignitas Clinic in Switzerland. This model would reduce the intensity of public opposition and gain public confidence by providing citizens with robust end-of-life options and the assurances they require. Finally, the paper argues that trisectoral policy partnerships are an appealing means for dealing with controversial policies imbued with symbolic meaning. Cet article analyse la faisabilité d’un partenariat réunissant les secteurs public, sans but lucratif et privé dans le but de gérer les questions controversées et symboliques que soulève la mise en place d’un service de suicide assisté en Ontario. Dans un premier temps, nous présentons les principales caractéristiques des relations solides et intégrées qui existent entre ces trois secteurs. Puis, nous définissons les paramètres d’une politique acceptable. Pour cela, nous examinons le point de convergence entre les moteurs de l’économie et l’opinion publique sur le suicide assisté : le gouvernement de l’Ontario est résolu à réduire les dépenses de santé, tandis que l’opinion publique se montre de plus en plus favorable aux options de fin de vie, mais craint que l’État ne fasse pression sur les malades pour les inciter à choisir une mort prématurée et ainsi éviter des interventions médicales coûteuses. Nous nous appuyons ensuite sur la structure de l’établissement suisse Dignitas pour démontrer comment un partenariat entre les trois secteurs pourrait servir de modèle en vue d’une politique et d’un service de suicide assisté en Ontario. Un tel modèle permettrait d’atténuer l’opposition du public et d’accroître la confiance des citoyens, grâce à des options de fin de vie fiables assorties des garanties requises. Pour conclure, nous avançons que les partenariats entre les trois secteurs constituent un moyen intéressant de gérer les politiques à forte charge litigieuse et symbolique.